Tilapia Piscidin 4 (TP4) Reprograms M1 Macrophages to M2 Phenotypes in Cell Models of Gardnerella vaginalis-Induced Vaginosis - Liu, Chia-Wen; Su, Bor-Chyuan; Chen, Jyh-Yih (Frontiers in Immunology, 2021)
Gardnerella vaginalis is associated with bacterial vaginosis (BV). The virulence factors produced by G. vaginalis are known to stimulate vaginal mucosal immune response, which is largely driven by activated macrophages. While Tilapia piscidin 4 (TP4), an antimicrobial peptide isolated from Nile tilapia, is known to display a broad range of antibacterial functions, it is unclear whether TP4 can affect macrophage polarization in the context of BV. In this study, we used the culture supernatants from G. vaginalis to stimulate differentiation of THP-1 and Raw264.7 cells to an M1 phenotype. The treatment activated the NF-κB/STAT1 signaling pathway, induced reactive nitrogen and oxygen species, and upregulated inflammatory mediators. Then, we treated the induced M1 macrophages directly with a non-toxic dose of TP4 or co-cultured the M1 macrophages with TP4-treated vaginal epithelial VK2 cells. The results showed that TP4 could not only decrease pro-inflammatory mediators in the M1 macrophages, but it also enriched markers of M2 macrophages. Further, we found that direct treatment with TP4 switched M1 macrophages toward a resolving M2c phenotype via the MAPK/ERK pathway and IL-10-STAT3 signaling. On the other hand, tissue repair M2a macrophages were induced by TP4-treated VK2 cells; TP4 upregulated TSG-6 in VK2 cells, which subsequently activated STAT6 and M2a-related gene expression in the macrophages. In conclusion, our results imply that TP4 may be able to attenuate the virulence of G. vaginalis by inducing resolving M2c and tissue repair M2a macrophage polarizations, suggesting a novel strategy for BV therapy.